Madrasah Strategy in Responding to Social Change in Society; A Case Study in Yogyakarta - Salim, Ahmad (The Magister of Islamic Education IAIN Pontianak, 2025)
Empathy and respect are two dominant behaviors of several values that have declined in mountain communities that should be closely related to these noble values. MAN 3 Kulon Progo, located in the Kulon Progo mountains of Yogyakarta, implements several activities to respond to changes in community values. This study aims to reveal the madrasah's strategy in strengthening empathy and respect values in students with a qualitative method using Lickona's theory. The author collected data through observation and interviews with 30 respondents consisting of 25 students, 1 vice principal, 3 PAI teachers and 1 BK teacher. The results of the study showed that empathy and respect values were strengthened through several activities in and outside the classroom. These two activities strengthen each other so that they can strengthen students' behavior in dealing with changes in community values.